Analisis Pendidikan Karakter Disiplin Melalui Budaya Sekolah pada Siswa SD GMIT 007 Kabola - Benyamin Oulaana; Jon A. Lalang Yame; Ardison Padafing; Ade Melisa Koilhing; Hia Adevia Lau; Hosiana Dollo Weni (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The main outcome of this study is the relatively low implementation of discipline-focused education through school days, so that any implementation of discipline-focused education through school days can more effectively discipline students, whether in schools, homes, or the general public. This study is conducted using a kualitatif approach. The purpose of this study is to analyze and describe the discipline-specific teaching methods used by the students of Sekolah Dasar. These studies are conducted using a deskriptif kualitatif approach with school principals, teachers, and students as the subjects. Studying is done in SD GMIT 007 KABOLA. In this study, observations, interviews, and documentation are used as data sources. The techniques for data analysis using the Miles and Huberman model include data redaction, data processing, and verification, or kesimpulan. Triangulation technique is used in the data elucidation process. The study's findings indicate that when it comes toTriangulation is a technique used in data analysis. The results of the study indicate that the following steps should be taken in order to implement the disciplined learning program through the school day at SD GMIT 007 KABOLA: 1) creating the character education program; 2) creating the school rules and behavior codes; 3) providing moral guidance to students in the elementary and middle schools; 4) involving parents/guardians in the disciplined learning process; and 5) involving the school committee in the disciplined learning process.